2021
DOI: 10.3389/fonc.2020.619622
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Cardiovascular Death in Breast Cancer Patients Without Chemotherapy or (and) Radiotherapy: A Large Population-Based Study

Abstract: BackgroundCardiovascular death (CVD) in breast cancer patients without chemotherapy (CT) or (and) radiotherapy (RT) has not been studied yet. This study evaluates the correlation between breast cancer and CVD risk independent of chemotherapy or (and) radiotherapy.MethodsData of female breast cancer patients without receiving CT or RT were retrieved from the Surveillance, Epidemiology, and End Result (SEER) database (2004–2015). Data were divided into two cohorts: tumor resection cohort and no resection cohort.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Furthermore, Guan et al reported that the tumor itself, not just the cardiotoxicity of radiotherapy, might increase the incidence of CVD deaths in patients who did not undergo radiotherapy. 20 , 31 Given these findings, the limitations of the present study led to the misconception that radiotherapy reduced CVD deaths in patients with breast, thyroid, and colorectal cancers.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Furthermore, Guan et al reported that the tumor itself, not just the cardiotoxicity of radiotherapy, might increase the incidence of CVD deaths in patients who did not undergo radiotherapy. 20 , 31 Given these findings, the limitations of the present study led to the misconception that radiotherapy reduced CVD deaths in patients with breast, thyroid, and colorectal cancers.…”
Section: Discussionmentioning
confidence: 85%
“… 14 , 15 , 16 , 17 , 18 However, some previous studies have also reported that the incidence of CVD deaths among patients with cancer is not elevated. 19 , 20 , 21 Hence, a unified conclusion on the relationship between radiotherapy and CVD deaths in patients with solid tumors has not yet been reached. In addition, knowledge of the tumors that increase the incidence of CVD deaths after radiotherapy is particularly important.…”
Section: Discussionmentioning
confidence: 99%
“…22 According to cardio-oncologists, cardiotoxic therapies (including chemotherapy or radiotherapy) are the main contributors to an increase in CVD risk in BCS. 23 In a case-control study with 2168 women from Northern Europe with breast adenocarcinoma treated with radiotherapy, 24 each 7 Gy of radiation corresponded to an increase in cardiovascular risk of 7.4%. The risk was observed 5 years after receiving radiotherapy and persisted for 30 years.…”
Section: Discussionmentioning
confidence: 99%
“…The 1:1 propensity score matching (PSM) and statistical analyses were executed by SPSS version 24 (SPSS, Chicago, IL). The 1:1 PSM was executed referring to our previous methods ( 16 ) by baseline characteristics at enrollment such as age at diagnosis, age of surgery, disease duration, follow-up time, levels of systolic/diastolic blood pressure (SBP/DBP) and heart rate (Hr), surgical intervention, cardiac valve damage, NYHA, medical condition, combined medication, blood test index, and echocardiographic index. The caliper width was 0.1 for PSM.…”
Section: Methodsmentioning
confidence: 99%